Correlation between the outer flow and the turbulent production in a boundary layer - Cliff, William C., author; Sandborn, Virgil A., author; National Aeronautics and Space Administration, publisher (Colorado State University. Libraries, 1975)
Space-time velocity correlation measurements between fluctuations occurring in the convoluting outer edge of a flat plate boundary layer with fluctuations occurring near the viscous subregion have been performed. The correlations indicate that information is propagated from the outer region to the inner region. The migration of turbulence away from the wall has been previously studied in the open literature. The results presented in this report along with the migration results lend support to the "limit cycle" model for turbulence production.
CER74-75WCC-VAS19.
May 1975.
Keywords: Boundary layer (Meteorology) -- Observations; Autocorrelation (Statistics)